IMPLEMENTATION OF COOPERATIVE LEARNING ASSISTED WITH TRADITIONAL GAME MEDIA IN IMPROVING STUDENT LEARNING OUTCOMES - Fajri, Zaenol; Sajuri, Sajuri; Aini, Qurratul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Early childhood is a busy and vital time for maximizing different cognitive skills so children can grow into good people. The capacity and awareness of teachers to take advantage of opportunities in this golden era depends on the success or failure of developing children's intelligence. Applying cooperative learning with traditional game media is a suitable alternative for early childhood education. Teachers must be able to choose and implement learning strategies most appropriate to the early childhood development level. This study aims to determine whether cooperative learning, aided by traditional game media, has improved learning results in Pancasila Bondowoso Kindergarten. This class action study uses observational tools, interviews, and recordings. The findings demonstrated students' enthusiasm and passion for learning and a substantial improvement in student learning outcomes from cycle 1 to cycle 3. The first cycle's learning outcomes were improved by 63% in the second cycle, to 74%, and by another 85% in the third cycle. Therefore, Bondowoso Pancasila Kindergarten's classroom action study on adopting cooperative learning supported by traditional game media in early childhood was deemed successful.